Initial experience with telemonitoring in left ventricular assist device patients - Hohmann, Stephan (J Thorac Dis, 2019)
BACKGROUND: Left ventricular assist devices (LVAD) are increasingly used in patients with end stage heart failure. The HeartAssist 5 and aVAD LVADs offer telemetric monitoring capabilities. Here we report our initial single centre experience with the largest telemonitoring cohort of LVAD patients. METHODS: Eleven patients (9 males) received a telemonitoring-capable LVAD and were included in our telemonitoring cohort. Waveforms and alarm data were obtained from the telemonitoring system and hospital records were reviewed for clinical data. RESULTS: Mean age at LVAD implantation was 59±5.1 years (mean ± standard deviation). Seven patients had non-ischemic cardiomyopathy and 4 patients had ischemic cardiomyopathy. Median LVEF at implant was 16% (IQR, 15–20%). The total follow-up time was 2,438 patient-days. A total of 6,216 alarm messages were generated in 11 patients. Most common were low flow alarms due to hypovolemia, followed by low flow alarms because of suspected pump thrombosis. One patient died during follow-up, one received a cardiac transplant and one had the LVAD explanted because of pump thrombosis. Pump thrombosis was suspected in 5 patients with 8 episodes of sudden flow decreases and laboratory signs of haemolysis. CONCLUSIONS: Real-time telemonitoring of LVAD pump flow, motor speed and power consumption is a promising tool in the follow-up of LVAD recipients. Trending pump flow over hours or days can assist in the early detection of complications, especially flow reductions due to hypovolemia and LVAD thrombosis. Further studies are warranted to delineate the impact of remote monitoring on patients’ prognosis.